Genome-Wide Assessment of the Association of Rare and Common Copy Number Variations to Testicular Germ Cell Cancer - Edsgärd, Daniel; Dalgaard, Marlene; Weinhold, Nils; Wesolowska, Agata; Rajpert-De Meyts, Ewa; Ottesen, Anne Marie; Juul, Anders; Skakkebæk, Niels E.; Skøt Jensen, Thomas; Gupta, Ramneek; Leffers, Henrik; Brunak, Søren (Frontiers in Endocrinology, 2013)
Testicular germ cell cancer (TGCC) is one of the most heritable forms of cancer. Previous genome-wide association studies have focused on single nucleotide polymorphisms (SNPs), largely ignoring the influence of copy number variants (CNVs). Here we present a genome-wide study of copy number variation on a cohort of 212 cases and 437 controls from Denmark, which was genotyped at ~1.8 million markers, half of which were non-polymorphic copy number markers. No association of common variants were found, whereas analysis of rare variants (present in less than 1% of the samples) initially indicated a single gene with significantly higher accumulation of rare CNVs in cases as compared to controls, at the gene PTPN1 (P=3.8*10-2, 0.9% of cases and 0% of controls). However, the CNV could not be verified by qPCR in the affected samples. The CNV calling of the array data was validated by sequencing of the GSTM1 gene, which showed that the CNV frequency was in complete agreement between the two platforms. This study therefore disconfirms the hypothesis that there exists a single CNV locus with a major effect size that predisposes to TGCC. Genome-wide pathway association analysis indicated a weak association of rare CNVs related to cell migration (FDR=0.021, 1.8% of cases and 1.1% of controls). Dysregulation during migration of primordial germ cells has previously been suspected to be a part of TGCC development and this set of multiple rare variants may thereby have a minor contribution to an increased susceptibility of TGCCs.